El uso de las tics para el desarrollo de vocabulario del idioma inglés. - Reinoso Nagua, Dennis Alexander (Machala: Universidad Técnica de Machala, 2025)
The objective of this research was to implement a system of didactic workshops with the use of the digital tool Lyrics Training, in order to improve the development of English vocabulary in the students of the 9th year of General Basic Education parallel “A” of the High School N/N of the city of Machala, during the school year 2025-2026. The scientific problem focused on identifying effective strategies to overcome the limitations in the management of English vocabulary, which negatively affect the linguistic competence of students. A quantitative approach was adopted under an explanatory experimental design, with a population of 22 students. The research employed theoretical methods such as historical-logical, analytical-synthetic and systemic, as well as empirical methods that included measurement, observation, interview and a diagnostic evaluation. The proposal consisted of the creation and implementation of a system of didactic workshops that integrated interactive technological resources to address different dimensions of vocabulary. The results obtained reflect a significant improvement in the acquisition and use of English vocabulary, showing progress in comprehension and contextual application. However, aspects that require further attention were identified, especially in the semantic and pragmatic use of the language, suggesting the relevance of including activities that encourage more reflective and autonomous learning in future proposals.
La presente investigación tuvo como objetivo implementar un sistema de talleres didácticos con el uso de la herramienta digital Lyrics Training, con el fin de mejorar el desarrollo del vocabulario en inglés en los estudiantes del 9no año de Educación General Básica paralelo “A” del Colegio de Bachillerato N/N de la ciudad de Machala, durante el periodo lectivo 2025-2026. El problema científico se centró en identificar estrategias efectivas para superar las limitaciones en el manejo del vocabulario en inglés, que inciden negativamente en la competencia lingüística de los estudiantes. Se adoptó un enfoque cuantitativo bajo un diseño experimental de tipo explicativo, con una población conformada por 22 estudiantes. La investigación empleó métodos teóricos como el histórico-lógico, analítico-sintético y sistémico, así como métodos empíricos que incluyeron medición, observación, entrevista y una evaluación diagnóstica. La propuesta consistió en la creación e implementación de un sistema de talleres didácticos que integró recursos tecnológicos interactivos para abordar diferentes dimensiones del vocabulario. Los resultados obtenidos reflejan una mejora significativa en la adquisición y uso del léxico en inglés, evidenciando avances en la comprensión y aplicación contextual. No obstante, se identificaron aspectos que requieren mayor atención, especialmente en el uso semántico y pragmático del idioma, lo que sugiere la pertinencia de incluir actividades que fomenten un aprendizaje más reflexivo y autónomo en futuras propuestas.
Keywords: DESARROLLO DE VOCABULARIO; INGLES; TALLERES DIDÁCTICOS; TECNOLOGIAS EDUCATIVAS; ENSEÑANZA BÁSICA